X-ray Dark-field Radiography - In-Vivo Diagnosis of Lung Cancer in Mice - Scherer, Kai; Yaroshenko, Andre; Boeluekbas, Deniz Ali; Gromann, Lukas B.; Hellbach, Katharina; Meinel, Felix G.; Braunagel, Margarita; Von Berg, Jens; Eickelberg, Oliver; Reiser, Maximilian F.; Pfeiffer, Franz; Meiners, Silke; et al. (Scientific Reports, 2017)
Accounting for about 1.5 million deaths annually, lung cancer is the prevailing cause of cancer deaths worldwide, mostly associated with long-term smoking effects. Numerous small-animal studies are performed currently in order to better understand the pathogenesis of the disease and to develop treatment strategies. Within this letter, we propose to exploit X-ray dark-field imaging as a novel diagnostic tool for the detection of lung cancer on projection radiographs. Here, we demonstrate in living mice bearing lung tumors, that X-ray dark-field radiography provides significantly improved lung tumor detection rates without increasing the number of false-positives, especially in the case of small and superimposed nodules, when compared to conventional absorption-based imaging. While this method still needs to be adapted to larger mammals and finally humans, the technique presented here can already serve as a valuable tool in evaluating novel lung cancer therapies, tested in mice and other small animal models.
CRIS-Team Scopus Importer:2023-03-08